Task performance and adaptive performance in Royal Service Corps: Role of individual ambidexterity and extent of change / Muhamad Fadzly Abd Kadir - Muhamad Fadzly, Abd Kadir (2020)
The Revolution in Military Logistics has impacted military logistics business processes. It requires logisticians to adapt to changes and perform their tasks. However, it also resulted in inconsistent performance of employees. The purpose of this study is to investigate the relationship between individual and situational factors and individual work performance of logisticians at the Royal Service Corps of the Malaysian Army. Individual factors (i.e. openness to experience and social intelligence) and a situational factor (i.e. workplace relationship) are the independent variables. Individual ambidexterity acts as a mediating variable, and the extent of change acts as a moderating factor. The dependent variables are individual work performance (task and adaptive performance). The theory of work performance and Burke–Litwin model are used to define concepts and explain the phenomena. Employee capacity, willingness and opportunity towards performance are assumed to have a significant relationship, and organisational environments are perceived and interpreted by their employees. Results of this study provide empirical evidence that the individual and situational factors have a significant relationship with task and adaptive performance, except for openness to experience and adaptive performance, which has a non-significant relationship. Individual ambidexterity behaviour among logisticians is pertinent to the individual factors but not to the situational factor in mediating job performance. The extent of change strengthens the relationship between individual ambidexterity behaviour and task performance and not with adaptive performance. Findings from this study have implications on the selection process, mixture and redeployment of personnel; training and competency development; and overall organisational improvement.